Partial Mediation of Job Satisfaction in Host Live Performance : Mediasi Parsial Kepuasan Kerja pada Kinerja Host Live - Deasy Fitria Kusmawati; Hesty Prima Rini (Academia Open, 2026)
General Background: Live shopping requires capable human resources because live hosts are directly involved in real-time consumer interaction, product presentation, and maintaining performance during streaming activities. Specific Background: The study context shows a consistent decline in live host performance throughout 2025, accompanied by indications of declining motivation and perceived inequity in the compensation system. Knowledge Gap: Previous research has shown inconsistent relationships between motivation, compensation, and employee performance, indicating the need to examine job satisfaction as a mediating variable in the relationship with live host performance. Aims: This study aims to examine the relationships of motivation and compensation with live host performance and investigate the mediating role of job satisfaction. Results: A quantitative causal-associative design was employed with 45 active live hosts selected through saturated sampling. Data were collected using a five-point Likert questionnaire and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). Motivation demonstrated a positive and significant relationship with performance (β = 0.296; p = 0.003), while compensation also demonstrated a positive and significant relationship with performance (β = 0.322; p = 0.000). Job satisfaction partially mediated the relationships of motivation (β = 0.209; p = 0.004) and compensation (β = 0.139; p = 0.013) with performance. Novelty: This study positions job satisfaction as a partial mediator between motivation, compensation, and live host performance in the digital creative industry. Implications: The findings provide theoretical contributions to human resource management and practical considerations for sustaining live host performance Highlights: Challenging work emerged as the dominant motivation factor. Workplace facilities were the dominant compensation factor. Supervision represented the dominant job satisfaction factor. Keywords: Motivation, Compensation, Job Satisfaction, Performance, Host Live